Testimonial Ecology in Gioconda Belli’s El país de las mujeres - Joel Postema (Studies in 20th & 21st Century Literature, 2015)
This article provides an analysis of the intersection between testimonial literature, ecological commentary, and feminist ideology as presented in Gioconda Belli’s 2010 novel El país de las mujeres.
Keywords: Gioconda Belli; Testimonial Literature; testimonio; Nicaragua; Ecocriticism; El país de las mujeres